A comparison of orthodontic elastic forces: Focus on reduced inventory - Ameerah Y Mansour (Wolters Kluwer Medknow Publications, 2017)
Objectives: To compare orthodontic elastics with different force extension characteristics, thereby aiming to reduce the orthodontist's inventory for elastics. Materials And Methods: Thirty nonextraction class I models were used to determine extension distances. Light, medium, and heavy forced Latex elastics of size 1/4 and 3/16 (from three manufacturers) were used. Thirty elastics from each pack were selected, for a total sample size of 540 elastics. Elastic force was measured at three extensions: three times the lumen (A), first molar to opposing canine (B), and second molar to opposing canine distance (C). Force values were compared with the analysis of variance followed by the post hoc Scheffe test. Results: Mean distance for extensions B and C were 22.3 and 38.7 mm, respectively. There was a continuous but significant increase in the force of 1/4 elastics when stretched from A to extension C. A significant increase in the force level of 3/16 elastics was only noted when stretched from A to B. Overall, 1/4 elastics had a wider range of force coverage in the extensions used, compared to 3/16 elastics. Conclusions: The use of 1/4 elastics is sufficient to cover the range of forces in orthodontic treatment.